Bilingual Processing Mechanisms of Scientific Metaphors and Conventional Metaphors: Evidence via a Contrastive Event-Related Potentials Study - Tang, Xuemei; Shen, Lexian; Yang, Peng; Huang, Yanhong; Huang, Shaojuan; Huang, Min; Ren, Wei (Frontiers in Psychology, 2022)
In order to study the different mechanisms of understanding figurative language in a speaker’s native language (L1) and his/her second language (L2), the current paper investigated how scientific metaphors in Chinese (L1) and English (L2) are electrophysiologically processed via ERP experimentation. Compared with metaphors from daily life or in literary works, scientific metaphors tend to involve both a more complicated context structure and a distinct knowledge-inferencing process. During the N400 time window (300-500ms), English scientific metaphors elicited more negative N400s than Chinese ones at the parietal region. In the LPC time window (550-800ms), English scientific metaphors elicited less positive LPCs than Chinese ones at the parietal region, and larger late negativities encompassing smaller areas of the brain. The findings might indicate that for late unbalanced bilingual speakers, L2 scientific metaphor comprehension requires more effort in information retrieval or access to the non-literal route. Altogether, the possible findings are that non-native and non-dominant language processing involves decreased automaticity of cognitive mechanisms, and decreased sensitivity to the levels of conventionality of metaphoric meanings.